2017
DOI: 10.1186/s13741-017-0066-3
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pulmonary complications after thoracic and abdominal surgery and associated risk factors in patients admitted at a government hospital in Harare, Zimbabwe-a retrospective study

Abstract: BackgroundThe burden of HIV/AIDS in Sub-Saharan Africa has presented unusual and challenging acute surgical problems across all specialties. Thoraco-abdominal surgery cuts through muscle and thereby disrupts the normal anatomy and activity of the respiratory muscles leading to reduced lung volumes and putting the patients at greater risk of developing post-operative pulmonary complications (PPCs). PPCs remain an important cause of post-operative morbidity, mortality, and impacts on the long-term outcomes of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
3
7
1
1
Order By: Relevance
“…Surgical duration longer than 3 hours would be 11 times more likely to have postoperative pulmonary complications ( p ≤ 0.001, AOR: 11.7, 95% CI: 3.62–38.03). This finding is in line with different pieces of the literature studied by different researchers abroad [ 3 , 12 , 15 ]. The possible explanation may be the long duration of surgery was associated with an altered physiological response of metabolic activities [ 13 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Surgical duration longer than 3 hours would be 11 times more likely to have postoperative pulmonary complications ( p ≤ 0.001, AOR: 11.7, 95% CI: 3.62–38.03). This finding is in line with different pieces of the literature studied by different researchers abroad [ 3 , 12 , 15 ]. The possible explanation may be the long duration of surgery was associated with an altered physiological response of metabolic activities [ 13 , 25 ].…”
Section: Discussionsupporting
confidence: 90%
“…Several works of the literature showed a wide variation in the occurrence of postoperative pulmonary complications ranging from 5 to 60% [ 1 , 3 23 ]. Variation of definitions, preoperative tests to identify the associated risk, criteria used to diagnose, and diverse populations in different countries were the major contributory factors for developing postoperative pulmonary complications in a wide range [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…No research has been found in the literature to investigate this relationship. The presence of atelectasis is a pathology that will cause problems in both operative and postoperative procedures for almost any type of surgery performed under general anesthesia.This negative relationship has been addressed in many studies and the importance of correcting this pathology preoperatively with various cautions has been highlighted [10][11][12]. Also parallel to the studies known so far, it has also been demonstrated that even band atelectasis is a risk for postoperative hypoxemia.…”
Section: Discussionmentioning
confidence: 95%
“…Özellikle büyük cerrahi girişimlerin (toraks ve batın cerrahisi gibi) sonrasında solunum komplikasyonları %12.5-%54.5 arasında değişen oranlarda görülmekte olup, cerrahi insizyonun diyafragmaya yakın olması durumunda bu oranların arttığı bildirilmektedir [6][7][8][9] . Literatürde torasik ve abdominal cerrahide %42.4 10 , torasik cerrahide %6.2 11 , üst abdominal cerrahide %20 12 oranında solunum komplikasyonlarının görüldüğü bildirilmektedir. Ameliyat sonrası dönemde görülen solunum komplikasyonları arasında sıklıkla atelektazi ve enfeksiyonlar (akut bronşit, pnömoni gibi) yer almaktadır [13][14][15] .…”
Section: Introductionunclassified